Procedure for Handling 4-H Accounts: Duties of the 4-H Unit Treasurer - Marilyn Norman; Joy C. Jordan (EDIS)
Revised! 4-H 5.8, a 1-page fact sheet by Marilyn Norman and Joy C. Jordan, describes the duties of the 4-H county or unit treasurer. Includes reference. Published by the Florida 4-H Program, October 2009.